2008
DOI: 10.1080/10408390701719355
|View full text |Cite
|
Sign up to set email alerts
|

How Safe is Vitamin E Supplementation?

Abstract: The safety of large doses of vitamin E went virtually unquestioned until the early 2000s, when several studies were published showing that consumption of vitamin E from dietary supplements increased mortality, as well as the risk of gastrointestinal cancer and heart failure. These studies prompted numerous letters to the editors of medical journals and widespread coverage in the media. Both the medical community and the general public became confused and concerned about the use of vitamin E supplements. The pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 59 publications
(165 reference statements)
0
25
0
Order By: Relevance
“…Besides the absence of accurate analysis of blood levels of supplemented form(s) and other forms present in blood and tissues, all main clinical trials were based on α-TOH supplementation at dosages usually higher than 200 mg/day. It is now emerging that high doses of vitamin E, administered as α-TOH, could interfere with the α-TTP dependent blood transferring and CYP metabolism of minor forms and particularly of γ-TOH, potentially leading to a specific secondary deficit of this form of vitamin E, which may have unfavorable effects in certain diseases [8,41]. In fact, specific biological properties of γ-TOH have been described such as higher efficacy in protecting from the NO-derived species peroxynitrite [3,42] and cell kinase regulation [43], which may explain how the relative abundance in plasma of this form has been associated with the reduced incidence of CHD [10,11] and prostate cancer [12].…”
Section: Discussionmentioning
confidence: 99%
“…Besides the absence of accurate analysis of blood levels of supplemented form(s) and other forms present in blood and tissues, all main clinical trials were based on α-TOH supplementation at dosages usually higher than 200 mg/day. It is now emerging that high doses of vitamin E, administered as α-TOH, could interfere with the α-TTP dependent blood transferring and CYP metabolism of minor forms and particularly of γ-TOH, potentially leading to a specific secondary deficit of this form of vitamin E, which may have unfavorable effects in certain diseases [8,41]. In fact, specific biological properties of γ-TOH have been described such as higher efficacy in protecting from the NO-derived species peroxynitrite [3,42] and cell kinase regulation [43], which may explain how the relative abundance in plasma of this form has been associated with the reduced incidence of CHD [10,11] and prostate cancer [12].…”
Section: Discussionmentioning
confidence: 99%
“…Though one study found that daily dose of 400 IU vitamin E may be deleterious in patients with vascular disease or diabetes mellitus [27], the majority of studies have shown that daily vitamin E supplementation of less than 1000 IU was safe in healthy individuals and may lead to reduced risks of cardiovascular disease, colon and prostate cancers, and poor cognition [28,29]. Furthermore, a dose of 400 IU was efficient in improving cardiovascular parameters [19].…”
Section: Supplementary Dosesmentioning
confidence: 99%
“…α-Toc exhibits 100% biological activity of vitamin E. β-, γ-, and δ-Toc have only 30%, 15%, and 5% biological activity, respectively (Traber, 2006). Toc confers several human health benefits, including a decreased risk of cardiovascular diseases, improved immune function, and a slower progression of degenerative conditions, such as cataracts, arthritis, and age-related disorders of the nervous system (Traber and Sies, 1996;Pryor, 2000;Bell and Grochoski, 2008). Recent reports suggest that vitamin E (Toc) intake, either from the diet or from supplements, may reduce the risk of liver cancer (Zhang et al, 2012;Hussain et al, 2013a).…”
Section: Introductionmentioning
confidence: 99%